Impact of choice of feeding tubes on long-term swallow function following chemoradiotherapy for oropharyngeal carcinoma. (3rd August 2019) - Prestwich, Robin J. D.; Murray, Louise J.; Williams, Gillian F.; Tease, Emma; Taylor, Lucy; George, Cathryn; Cardale, Kate; Dyker, Karen E.; Murray, Patrick; Sen, Mehmet; Ramasamy, Satiavani
Abstract: Background: Prior reports have raised concerns that a prophylactic gastrostomy may be detrimental to long-term swallow function. This study evaluates patient-reported swallow function following chemoradiotherapy for oropharyngeal carcinoma in relation to the use of a prophylactic gastrostomy or nasogastric (NG) tube as required. Material and methods: The MD Anderson Dysphagia Inventory (MDADI) was posted to 204 disease-free patients at least 2 years following chemoradiotherapy for oropharyngeal carcinoma between 2010 and 2014. Results: Overall, 181/204 (89%) patients returned questionnaire at a median of 34 months post-treatment. 97/181 (54%) and 84/181 (46%) were managed with an approach of a prophylactic gastrostomy or NG tube as required, respectively. A prophylactic gastrostomy was associated with higher rates of enteral feeding (92% vs. 58%, p  < .001), lower median percentage weight loss (7.0% vs. 9.4%, p  < .001), increased duration of enteral feed (median 3.3 vs. 1.1 months, p  < .001). There was no significant difference in patient-reported swallow function measured by MDADI summary scores and subscales for patients managed with an approach of prophylactic gastrostomy or NG as required. Duration of enteral feed correlated negatively with composite MDADI scores. A subgroup of 116/181 (64%) patients were documented as having been offered a choice of enteral feeding approach and therefore can be considered to represent clinical equipoise; there were no significant differences in MDADI scores according to route. Conclusions: Despite concern regarding the use of a prophylactic gastrostomy in prior studies, the approaches of using a prophylactic gastrostomy or an NG tube as required to support patients during/after chemoradiotherapy for oropharyngeal carcinoma were associated with similar long-term swallow outcomes.